A produção historiográfica sobre o Contestado (2001-2019) - Juraski, Vanderlei Cristiano (2021)
This thesis investigates the formation of a field of historical knowledge about the Contestado movement in the first two decades of the 21st century. The objective is to identify trends in historiography about the social conflicts that occurred in the Santa Catarina plateau, as well as the formation of a field of research on the subject. This endeavor is justified insofar as the examination of the set of theses on the subject is a contribution to historiographical analyses, capable of revealing elements that transcend studies on the Contestado. Among other aspects, we can mention the recent expansion of postgraduate courses in History in Brazil, the changes in the epistemology of Historical Science, and an institutional organization on the part of historians to debate the problem. The methodology used in this research is based on historiographical analysis, using as theoretical reference, especially, texts by Rüsen (2015), Ricoeur (1994) and Orlandi (2003 and 2005) and as sources the theses and interviews of fourteen PhDs in History whose object of study is the Contestado. Through this investigation, we observed the constitution of a field of knowledge, in the terms of Bourdieu (1989), and a community of historians who share certain interests, documentation, theoretical-methodological references and interpretations about the Contestado. In other words, the interactions between intellectuals are not limited to the production of theses, but extend to participation in committees, the elaboration of collective works and the organization of events. Their interpretations of the object under analysis converge on two main points. Initially, these authors highlight the Contestado as a fluid, dynamic movement, integrated with new social demands - not restricted to the war years (1912-1916). In addition, they emphasize the popular nature of the social movement, which opposed in different ways the expropriation of lands and the curtailment of rights such as respect for and preservation of the way of life of the caboclos in the Santa Catarina plateau. These findings were verified based on the examination of the theoretical perspectives, methods and narratives developed by historians and identified in the deficiencies and functions of guidance of the theses produced in postgraduate courses in History.